Plate 2: Case for producing inflammable gas - Faujas-de-St.-Fond, cit. (Barthélemy) (Description des expériences de la machine aérostatique de MM. de Montgolfier, 1783)
This case was designed by the Robert brothers, Anne-Jean (1758-1820) and Nicolas Louis (1761-1828) Robert to quickly produce large quantities of hydrogen gas through the reaction of sulfuric acid with iron filings. The wooden case was intended to optimize the surface area of iron exposed to the acid by distributing the process across five lead-lined drawers. Once filled, the drawers were to be immediately sealed by sliding them along a track, as shown in the engraving. The path of the gas from drawer to drawer could be controlled from the outside, allowing each drawer to be isolated in turn. Once produced, the hot gas would be cooled by being siphoned through water and eventually exhausted out the pipe at the top of the case. According to Faujas de Saint-Fond, the case did not work as intended: the drawers were not deep enough, the heat and humidity of the reaction warped the wood, and the hot gas could not make it through the column of cooling water. Nevertheless, Faujas de Saint-Fond included it in his book because he had already commissioned the engraving before he tried the machine; he also hoped that others might learn from the illustration and explanatory text and improve upon the overall design.
Keywords: Airships; Ballooning; Hot air balloons